If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(v + 1) = 6v + -48 Reorder the terms: -3(1 + v) = 6v + -48 (1 * -3 + v * -3) = 6v + -48 (-3 + -3v) = 6v + -48 Reorder the terms: -3 + -3v = -48 + 6v Solving -3 + -3v = -48 + 6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-6v' to each side of the equation. -3 + -3v + -6v = -48 + 6v + -6v Combine like terms: -3v + -6v = -9v -3 + -9v = -48 + 6v + -6v Combine like terms: 6v + -6v = 0 -3 + -9v = -48 + 0 -3 + -9v = -48 Add '3' to each side of the equation. -3 + 3 + -9v = -48 + 3 Combine like terms: -3 + 3 = 0 0 + -9v = -48 + 3 -9v = -48 + 3 Combine like terms: -48 + 3 = -45 -9v = -45 Divide each side by '-9'. v = 5 Simplifying v = 5
| (5b-9)-2(2b+3)=-4 | | (x-4)=(x+4) | | 4(2b+3)+6(3b+5)=70 | | y-wy=mfory | | 3u+3=6(u-1) | | x^5+3x^4-10x^3-30x^2+16x+48=0 | | -(5x-11)+3(6X+5)= | | -3(v-5)=-7v+7 | | 2X^2+3Y^2=10 | | 9x+11=5x+43 | | 6F+2+3F+10+F+5= | | 2w+4x+12y+7w+10x-4w=Equation | | 0.8=3 | | 1x=2x+2 | | -3(5p+5)-2(6-11p)=3(2+2p) | | a^2-32=-4a | | 12.75b=4 | | 90+112+73+x=360 | | 24y-22=-(1-6y) | | 8.2+x=23.4 | | -9(x-2)=8(x-3) | | 2x^2-38+180=0 | | F=(L-3)200 | | 9-x-x+8=0 | | -x+6=2x+18 | | 24=-(x-8) | | 2w+4x+12y+7w+10x-4w= | | 3m(7-21m)=0 | | 7x-y+49=0 | | 5(x+5)+5=5(x-8) | | 6x+8=4x-8 | | -22x-114-3x=-44x |